2021
DOI: 10.1109/jsen.2021.3075867
|View full text |Cite
|
Sign up to set email alerts
|

All-Fiber Fabry-Perot Interferometer Gas Refractive Index Sensor Based on Hole-Assisted One-Core Fiber and Vernier Effect

Abstract: A novel high sensitivity all-fiber Fabry-Perot interferometer (FPI) gas refractive index (RI) sensor based on hole-assisted one-core fiber (HAOCF) and Vernier effect was proposed and demonstrated. The sensor is fabricated by splicing a section of HAOCF to a section of silica tube (ST) fused with the lead-in single-mode fiber (SMF), ensuring that the sensor is composed of an air-cavity FPI and a silica-cavity FPI. The cascaded dual-cavities generate the Vernier effect due to a similar free spectrum range (FSR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 30 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Relatively weak RI variations (n<10 -7 RIU) induced by photothermal excitation of gas mixtures are at the limit of detection of established spectral interrogation methods, used for compact fiber-based FPIs [24], especially when the interrogation must be achieved dynamically at higher read-out rates. Thus, alternative methods were considered, and an interrogation was applied, based on a probe laser locking onto the quadrature point of the FPI transfer function.…”
Section: Signal Interrogationmentioning
confidence: 99%
“…Relatively weak RI variations (n<10 -7 RIU) induced by photothermal excitation of gas mixtures are at the limit of detection of established spectral interrogation methods, used for compact fiber-based FPIs [24], especially when the interrogation must be achieved dynamically at higher read-out rates. Thus, alternative methods were considered, and an interrogation was applied, based on a probe laser locking onto the quadrature point of the FPI transfer function.…”
Section: Signal Interrogationmentioning
confidence: 99%
“…The highest airflow velocity sensitivity of the sensor reached 1.541 nm/(m/s) in the region of 3∼7 m/s. In addition, many schemes similar to this structure have been reported, most of which combine the air cavity and the silica cavity to produce the Vernier effect [ 10 , 12 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. There are also some reports that employ the air cavity and the other cavity together [ 41 , 42 ].…”
Section: Configurations To Produce the Vernier Effectmentioning
confidence: 99%
“…In the last two decades, optical fiber sensors have been widely researched owing to the advantages of small size, long lifetime, strong flexibility, passive operation, and anti-electromagnetic interference. [7][8][9][10][11][12][13] It has been demonstrated that the refractive index (RI) correlates better with salinity better than conductivity. 14,15 Hence salinity sensors based on optical fiber techniques are preferable as promising alternatives due to their numerous advantages.…”
Section: Introductionmentioning
confidence: 99%